The several times I painted myself around: an analysis of self-portrait - Silva, Maria Betânia e; Silvestre, Beatriz Costa da Silva (Revista do Colóquio, 2023)
This work aims to present and analyze self-portraits taken between 2016 and 2021, with the aim of creating a reflection on the creative and memory process. In the first part, the debate addresses self-portrait and the historical context, with special attention to the end of the 19th and beginning of the 20th century. Secondly, the discussion focuses on what defines the self-portrait, what its creative process involves and how memory influences its production. To conclude, based on the self-portraits, an analysis was carried out, thinking mainly about the artistic and creative process involved in each of them.